2015
DOI: 10.1016/j.micres.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

MoARG1, MoARG5,6 and MoARG7 involved in arginine biosynthesis are essential for growth, conidiogenesis, sexual reproduction, and pathogenicity in Magnaporthe oryzae

Abstract: Arginine is one of the most versatile amino acids in eukaryote cells, which plays important roles in a multitude of processes such as protein synthesis, nitrogen metabolism, nitric oxide (NO) and urea biosynthesis. The de novo arginine biosynthesis pathway is conserved among fungal kingdom, but poorly understood in plant pathogenic fungi. Here, we characterized the functions of three synthetic enzyme-encoding genes MoARG1, MoARG5,6, and MoARG7, which involved the seventh step, second-third step and fifth step … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 45 publications
2
52
1
Order By: Relevance
“…Carbamoyl phosphate is produced by a branch of the de novo arginine biosynthesis pathway, and is synthesized and utilized to directly supplement ornithine (Pierard and Schroter, 1978; Davis, 1986), although the importance of arginine biosynthesis in organisms is still unknown. Zhang et al reported that three synthetic enzyme genes MoARG1, MoARG5,6 , and MoARG7 were involved in arginine biosynthesis and were required for the development and virulence of M. oryzae (Zhang et al, 2015). Therefore, further studies need to be conducted to explore the underlying mechanisms of arginine biosynthesis pathway in phytopathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Carbamoyl phosphate is produced by a branch of the de novo arginine biosynthesis pathway, and is synthesized and utilized to directly supplement ornithine (Pierard and Schroter, 1978; Davis, 1986), although the importance of arginine biosynthesis in organisms is still unknown. Zhang et al reported that three synthetic enzyme genes MoARG1, MoARG5,6 , and MoARG7 were involved in arginine biosynthesis and were required for the development and virulence of M. oryzae (Zhang et al, 2015). Therefore, further studies need to be conducted to explore the underlying mechanisms of arginine biosynthesis pathway in phytopathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Amino acids, such as arginine, methionine, leucine, isoleucine and valine, are essential for hyphal growth in phytopathogenic fungi [1719, 29]. To examine whether threonine is necessary for fungal viability, we observed hyphal growth of the cothr4 mutant on the synthetic defined (SD) media with or without threonine.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that multiple amino acids, such as arginine, isoleucine, leucine and methionine, are required for conidial development in M. oryzae and Fusarium graminearum [1719, 29]. Genome-wide gene expression profiling during conidiation in M. oryzae revealed the induction of many genes involved in amino acid transport [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the key metabolic enzymes for arginine and lysine synthesis are alternatively spliced. In plant and human pathogens, arginine and lysine synthesis are indispensable for fungal growth and pathogenicity (Zhang et al ., , Liebmann et al ., ). In B. bassiana , carbon catabolite repression factor plays important roles in the assimilation of exogenous nutrients and fungal virulence (Luo et al ., ) and is also affected by AS processes.…”
Section: Discussionmentioning
confidence: 99%